ADVANCED WATER TECHNOLOGIES concepts and applications. - Tewari, P. K. ([S.l.] : CRC PRESS, 2020)
The book explores basic concepts and advanced topics in the field of water technologies. It deals extensively with advances in materials, material selection, preparation, characterization and application. The relevance of water technologies in industries is considered, and a section is dedicated to describing and analyzing the technologies required for water reuse and advanced purification, including desalination. Nuclear desalination, low-carbon desalination and water purification technologies to address the adverse impacts of climate change are examined from both the adaptation and mitigation points of view. Aimed at senior undergraduate/graduate students in chemical, civil and environmental engineering, along with wastewater and desalination researchers, this book: Details advanced water treatments for varied processes. Describes membrane and desalination techniques for water reuse and advanced purification. Elaborates water technologies at both the front and back ends of the process. Discusses modern technologies for effluent treatment and water recycling. Explores the role of information technology in the water sector.
OCLC-licensed vendor bibliographic record.
Keywords: Water quality management; Water -- Purification; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Material Science